zero days, 3 hours + 20 min + 1 hour + 48 min = 308 min which is about 5 hours.
3 hours 20 minutes + 1 hour 48 minutes = 0.2139 days
Let’s calculate the total time in hours and minutes:
Add the hours: [tex]3 \text{ hours} + 1 \text{ hour} = 4 \text{ hours}[/tex]Add the minutes: [tex]20 \text{ minutes} + 48 \text{ minutes} = 68 \text{ minutes}[/tex]Now, let’s convert the total time to days:
1 day = 24 hours1 hour = 60 minutesFirst, convert the minutes to hours:
[tex]68 \text{ minutes} = \frac{68}{60} \text{ hours} = 1.1333 \text{ hours}[/tex]
Next, add the converted hours to the original 4 hours:
[tex]4 \text{ hours} + 1.1333 \text{ hours} = 5.1333 \text{ hours}[/tex]
Now, divide the total hours by 24 to find the equivalent days:
[tex]5.1333 \text{ hours} \div 24 = 0.2139 \text{ days}[/tex]
Therefore, 3 hours 20 minutes + 1 hour 48 minutes equals approximately 0.2139 days
One cell phone plan charges $0.08 per text and another plan charges $0.12 per text. What’s the simplified ratio of the cheaper plan to the more expensive plan?
A. 3:2
B. 8:12
C. 12:8
D. 2:3
Answer:
2/3
Step-by-step explanation:
That ratio, right out of the box, would be cheaper / more expensive, or $0.08 / $0.12. This can be reduced to 8/12, or 2/3.
What is the slope of the line that is graphed below ?
Rise over run, so 2/6. This can be simplified to 1/3. Hope this helps!
Answer: The SLOPE of the graphed line is [tex]\dfrac{1}{3}.[/tex]
Step-by-step explanation: We are given to find the slope of the graphed line in the figure.
From the graph, we note that
the line passes through the points (0, 2) and (6, 4).
We know that
the slope of a straight line passing through the points (a, b) and (c, d) is given by
[tex]m=\dfrac{d-b}{c-a}.[/tex]
Therefore, the slope of the graphed line is given by
[tex]m=\dfrac{4-2}{6-0}=\dfrac{2}{6}=\dfrac{1}{3}.[/tex]
Thus, the SLOPE of the graphed line is [tex]\dfrac{1}{3}.[/tex]
i ReAlLy NeEd HeLp PlZzZzZzZzZzZzZzZzZzZz
A and B because with the other three, they simplify to something else.
Nemili has 12 red triangles and 3 blue triangles how many more red triangles does Nemili have them blue triangles?
12 - 3 = 9
So Nemili has 9 more red triangles than blue triangles.
Hope this Helps!!
Eight less than a number is one-third the number. what is this in numerical form?
a) 8-n=n/3
b) n-8=3n
c) n-8=n/3
d)n/3-8=n
Eight less than a number = n - 8
One-third the number = 1/3 * n or n/3
So eight less than a number is one-third the number"
n - 8 = n/3
Answer is c) n-8 = n/3
NEED HELP ASAP, EASY PROBLEM! Number 4 pls
Six more than three times a number is less than or equal to 96. d. Five less then half the distance from Jerod’ s home to the mall is more then 6 miles
First statement : Six more than three times a number is less than or equal to 96.
Let us assume number be n.
We can repharse above statement as :
"6 more than 3 times of n is less than or equal to 96".
Therefore, we can write an ineuality as.
3 times of n = 3n
6 more than 3 times of n = 3n+6.
3n+6 ≤ 96.
_____________________________________________________________
Statement 2: Five less then half the distance from Jerod’ s home to the mall is more then 6 miles.
Let us distance from Jerod’ s home to the mall is d.
We can repharse above statement as:
5 less than 1/2 of d is more than 6 miles.
5 less than 1/2 of d = 1/2d -5 .
Therefore, we can write an ineuality as.
12d -5 > 6.
-10e+15=95-30e
solve the equation
Hey there!:
- 10 e + 15 = 95 - 30 e
subtract 15 from both sides:
- 10 e + 15 - 15 = 95 - 30 e - 15
Simplify :
- 10 e = - 30 e + 80
Add 30 e to both sides:
- 10 e + 30 e = - 30 e + 80 + 30 e
Simplify:
20 e = 80
e = 80 / 20
e = 4
hope that helps!
EMERGENCY
How do I find the axis of symmetry equation based on the graph?
Final answer:
The axis of symmetry of a parabola can be found by the formula x = -b/(2a), which uses the coefficients of the quadratic equation. This line runs vertically through the vertex of the parabola.
Explanation:
Finding the axis of symmetry for a quadratic equation based on its graph involves identifying the line that divides the parabola into two mirror images. The axis of symmetry is always a vertical line and can be found by looking at the vertex (the highest or lowest point) of the parabola. The equation for the axis of symmetry is x = h, where h is the x-coordinate of the vertex. If the quadratic equation is in the standard form y = ax² + bx + c, the axis of symmetry can be calculated using the formula x = -b/(2a).
For instance, if we have a quadratic equation like y = 2x² - 4x + 1, we can find the axis of symmetry by using the formula with a = 2 and b = -4 which gives us x = -(-4)/(2*2) = 1. Therefore, the axis of symmetry for this parabola is x = 1.
Hey guys can somebody help me please ? With all the questions
Sorry this is not the answer but I think it will help majorly it you can replace the unknown numbers with random ones and just keep on switching it out. Hope it helps a bit. :)
The answer to the riddle is I_SO_LATE_ME! (the underscores are the squares.
1. 3x+2=5 (o)
2. 4+9+5+x=2x (square)
3. x/4+7=12 (a)
4. 2x+3=12 (e)
5. 7x=42 (!)
6. x/5=3 (e)
7. 2x+3x+4=12 (s)
8. 3x-2=5 (square)
9.
10.
11.
12.
13.
please help me i really need help :;
The kinetic energy of the girl is 120 J while the dog has 40 J.
if the dog speeds up, it would have a kinetic energy of 160J.
In order to get these answers, you need to use the formua for kinetic energy which is KE=1/2 mv^2. mass=m, v=velocity and KE= Kinetic Energy.
Answers of tthe questions are reasonable because you would gain more energ if you run faster and also more energy if you gain more mass.
find an equation for the inverse relation y=-2x+5
[tex]replace y by x and vice versa, then solve for y:
y=-2x+5 \rightarrow x=-2y+5 \implies y=-\frac{1}{2}(x-5)[/tex]
What does the y-intercept and what does it indicate
The y-intercept is the point where the line crosses the vertical y-axis.
At the bank, Derek made 7 withdrawals, each in the same amount. His brother, John, made 5 withdrawals, each in the same amount. Each of John’s withdrawals was $5 more than each withdrawal that Derek made. Both Derek and John withdrew the same amount of money in the end. How much did each brother withdraw?
A) Write an equation. Let x represent the amount of one of Derek’s withdrawals. B) Solve the equation. Show your work.
C) Check your solution. Show your work. D) State the solution in complete sentences
Answer:
x=12.50
y = 17.50
Step-by-step explanation:
x = Amount of one Derek withdrawal
then amount of John withdrawal =x+5
Total withdrawals of Derek = no of times x one time withdrawal
= 7(x) = 7x ... i
No of John withdrawal = no of times x one time withdrawal
= 5(x+5) ... ii
Given that i and ii are equal
i.e. 7x =5(x+5)
7x = 5x+25
2x =25
x = 12.50 dollars
Y = 17.50 dollars
Checking part:
total derek withdrawal = 7(12.5) =87.50
Joh's withdrawal = 5(17.50) = 87.50
Since both are equal, our answers are right.
Solution: Derek withdrew each time 12.50 dollars each for 7 times and John withdrew 17.50 dollars each for 5 times.
Jose buys a bag of cookies that contains 6 chocolate chip cookies, 8 peanut butter cookies, 9 sugar cookies and 8 oatmeal cookies.
What is the probability that Jose reaches in the bag and randomly selects a peanut butter cookie from the bag, eats it, then reaches back in the bag and randomly selects a chocolate chip cookie?
approximately 5% of the time. In decmial form, it is 0.0516129032. If it is in fraction from, then it is 8/155. To explain, you find the total number of cookies. Then you find the number of peanut butter cookies and put that as the numerator over the total as the denominator. After that, you find the number of cookies left after Jose eats one cookie. That becomes the denominator and then find the amount of chocolate chip cookies ib the bag and put it over that total. Multiply both fractions together to get this answer.
The probability that Jose first selects a peanut butter cookie and then a chocolate chip cookie from a bag of 31 cookies is 8 out of 155.
Explanation:This problem is a question of probability, which is a branch of Mathematics. Probability determines how likely an event is to occur out of the total number of possible outcomes. We'll calculate it step by step:
First, we calculate the total number of cookies. Jose has 6 chocolate chip cookies, 8 peanut butter cookies, 9 sugar cookies and 8 oatmeal cookies. We add all these up to get the total number of cookies, which is 31 cookies.Then, Jose first selects a peanut butter cookie. The probability of this happening is the number of peanut butter cookies (8) divided by the total number of cookies (31). We simplify this to 8/31.After eating the peanut butter cookie, the total number of cookies is now 30 and the number of chocolate chip cookies remains 6. Thus, the probability of selecting a chocolate chip cookie now is 6/30, which simplifies to 1/5.Now, we multiply the two probability values to get the overall probability: 8/31 * 1/5 = 8/155. So, the probability that Jose first selects a peanut butter cookie and then a chocolate chip cookie is 8 out of 155.Learn more about Probability here:https://brainly.com/question/32117953
#SPJ3
Weight/Calories per Day 1000 to 1500 cal. 1500 to 2000 cal. 2000 to 2500 cal. Total
120 lb. 90 80 10 180
145 lb. 35 143 25 203
165 lb. 15 27 75 117
Total 140 250 110 500
Based on the data in the two-way table, what is the probability that a person consumes 1,500 to 2,000 calories in a day?
A. 0.22
B. 0.28
C. 0.35
D. 0.50
Option: D is the correct answer.
The probability is: 0.50
Step-by-step explanation:Weight/Calories 1000-1500 1500-2000 2000-2500 Total
120 lb. 90 80 10 180
145 lb. 35 143 25 203
165 lb. 15 27 75 117
Total 140 250 110 500
We are asked to find the probability that a person consumes 1500-2000 calories in a day.
Total number of people who were surveyed=500
Total number of people who consume 1500-2000 calories in a day are:250
Hence, Probability is:
250/500=1/2=0.50
Answer: D. 0.50
Step-by-step explanation:
Formula for probability :
[tex]\text{Probability}=\dfrac{\text{Favorable outcomes}}{\text{Total outcomes}}[/tex]
The given two-way table :
Weight/Calories 1000-1500 1500-2000 2000-2500 Total
120 lb. 90 80 10 180
145 lb. 35 143 25 203
165 lb. 15 27 75 117
Total 140 250 110 500
To find the probability that a person consumes 1500-2000 calories in a day., we need :
a) The total number of people surveyed. (Total outcomes)
b) The number of people consume 1500-2000 calories in a day. (favorable outcomes)
From the above table,
Total people surveyed=500
Number of people consume 1500-2000 calories in a day are=250
Then , the required probability will be :-
[tex]\text{P(person consumes 1,500 to 2,000 calories in a day)}=\dfrac{250}{500}=\dfrac{1}{2}\\\\=0.50[/tex]
Hence, the probability that a person consumes 1,500 to 2,000 calories in a day=0.50
One method to develop a plan for a proof is to work “backwards” by starting with the conclusion
Answer:
true
Step-by-step explanation:
Diver jumps from a distance that is 48 feet above the surface and stops descending 12 feet below the surface what was the length of her jump?
what is the factorization of the trinomial below -2x^3-2x^2+12x
-2x^3 - 2x^2 + 12x
Because we can pull out a common factor, we'll do that first to simplify the expression.
-2x(x^2 + x - 6)
Now, let's see if we can split the middle term.
Display factors of -6.
-6 * 1
-1 * 6
-3 * 2
3 * -2 (these digits satisfy the requirements for splitting the middle term)
Split the middle term.
-2x(x^2 + 3x - 2x - 6)
Group terms in pairs of two.
-2x((x^2 + 3x) - (2x - 6))
Factor each binomial.
-2x((x(x + 3)) - (2(x + 3)))
Rearrange the terms.
-2x(x - 2)(x + 3) is the fully factored form of the provided trinomial.
The factorization of the trinomial -2x^3-2x^2+12x includes first factoring out the common factor -2x, and then further factoring of the trinomial within the parenthesis results in the final factorization as -2x(x-2)(x+3).
Explanation:The trinomial in this question is -2x^3-2x^2+12x. The process we use to factor this trinomial would be to first factor out the greatest common factor (GCF) for all the terms. In this case, the GCF is -2x.
So, if we factor out -2x, we get: -2x(x^2+x-6). We can continue to factor the trinomial (x^2+x-6) inside the parenthesis then. We find that it factors to (x-2)(x+3).
Thus, the final factorization of the original trinomial is -2x(x-2)(x+3).
Learn more about Factorization here:https://brainly.com/question/33624529
#SPJ3
Which is the inverse of the function f(x) = x2 − 4?
The function is not one-to-one function, hence the inverse doesn't exist for the whole domain of the function. But if we restrict the domain to [tex]x\in(-\infty,0][/tex] or [tex]x\in[0,\infty)[/tex], then we can give the inverse.
[tex]f(x)=x^2-4\\\\y=x^2-4\\\\x^2=y+4\\\\x=\sqrt{y+4} \vee x=-\sqrt{y+4}\\\\f^{-1}(x)=\sqrt{x+4}\vee f^{-1}(x)=-\sqrt{x+4}[/tex]
So, when [tex]D_{f(x)}:x\in(-\infty,0][/tex], the inverse is [tex]f^{-1}(x)=-\sqrt{x+4}[/tex] and when [tex]D_{f(x)}:x\in[0,\infty)[/tex], the inverse is [tex]f^{-1}(x)=\sqrt{x+4}[/tex].
The inverse of the function f(x) = x^2 - 4 is found by switching the x and y variables and solving for y. Because y is being squared, there are two solutions: y = ±sqrt(x + 4).
Explanation:The inverse of a function f(x) is found by switching the x and y variables and solving for y. For the function f(x) = x^2 - 4, let us swap x and y, it becomes x = y^2 - 4. Next, solve for y. However, because y is being squared, there will be two solutions, one for the positive square root and other for the negative square root. Therefore, the inverse of the function f(x) = x^2 - 4 is y = ±sqrt(x + 4).
Learn more about Inverse Function here:https://brainly.com/question/17872426
#SPJ3
Re-write this subtraction as an ADDITION of signed numbers. 3 − 7
3 + (-7)
yyyyyyyyyyyyyyyy
The addition form will be equal to 3 + (-7).
What is an expression?
Expression in maths is defined as the collection of the numbers variables and functions by using signs like addition, subtraction, multiplication and division
Given that:-
= 3 − 7
The additional form of the above expression will be:-
=3 + (-7)
Therefore the addition form will be equal to 3 + (-7).
To know more about Expression follow
https://brainly.com/question/723406
#SPJ2
PLZ SHOW all WORK 40 points!!!!
Answer:
Kim is 24 and her sister is 12.
Step-by-step explanation:
a) Xx2+X
I used the variable X because that represents Kim's sisters age, which you need to know in order to find out Kim's age. To get Kim's sisters age use a guess and check table or pick numbers until you get to the correct answer.
b) 12x2=24
24+12=36
My solution is Kim is 24 and her sister is 12.
What are the slope and the y- intercept of the linear function
the slope is 9 and the y-intercept is - 2
the equation of a line in ' slope-intercept form ' is
y = mx + c ( m is the slope and c the y-intercept )
y = 9x - 2 is in this form
with slope m = 9 and y-intercept c = - 2
complete the sentence. 7 is ten times the value of __?
7 is ten times the value of 0.7
which term describes lines that intersects at a 90 degree angle?
The lines are Perpendicular
Perpendicular lines are lines that directly bisect each other, forming 90° angles
~Rise Above the Ordinary
Hi, I'n Jenny and I'm a mathematician! I'd love to help you! :)
"which term describes lines that intersects at a 90 degree angle? "
My answer: perpendicular lines
Attached is more info on math lines
Message from ExperimentsDIYS:
Our team aims to please and if you have any question regarding your topic, we are here to help! We know that your education is very important. <3
6 to the power of 2 add y to the power of 2 is r to the power of 2. what is r and y?
Subtract -a^2-5ab+3b^2 from 3a^2-2ab+3b^2
The correct answer is 4a^2 + 3ab
In order to find this, we can write the equation out as described and then follow the order of operations.
3a^2 - 2ab + 3b^2 - (-a^2 - 5ab + 3b^2) ----> Distribute the negative
3a^2 - 2ab + 3b^2 + a^2 + 5ab - 3b^2 ----> Combine like terms
4a^2 + 3ab
The subtraction -a² - 5ab + 3b² from 3a² -2ab + 3b² is -a(4a + 3b)
What is an Algebra?Algebra is the study of mathematical symbols and the rule involves manipulating these mathematical symbols.
What is Simplification?Simplification is to make something easier to do or understand and to make something less complicated.
Given
-a² - 5ab + 3b² and 3a² -2ab + 3b² are the two expression.
How to find the subtraction -a² - 5ab + 3b² from 3a² -2ab + 3b²?-a² - 5ab + 3b² from 3a² -2ab + 3b², we will have
-a² - 5ab + 3b² - (3a² -2ab + 3b²)
On simplifying,
-a² - 5ab + 3b² - 3a² + 2ab - 3b²
-4a² - 3ab
-a(4a + 3b)
Thus , the subraction is -a(4a + 3b).
More about the subtraction link is given below.
https://brainly.com/question/4319655
what is the x-intercept of the function graphed? help!
i believe your answer is c. because the x value goes first in a coordinate. hope this helps!
Which expression is equivalent to (x4/3x2/3)1/3
Given
The expression is given in the question
[tex]=(x^{\frac{4}{3}}\times\ x^{\frac{2}{3}})\ ^{\frac{1}{3}}[/tex]
Find the expression is equivalent to the above expression.
To proof
As expression is given in the question
[tex]=(x^{\frac{4}{3}}\times\ x^{\frac{2}{3}})\ ^{\frac{1}{3}}[/tex]
By using the properties
product of powers property tells us that when you multiply powers with the same base you just have to add the exponents.
i.e
[tex]x^{a} .x^{b} = x^{a +b}[/tex]
Now using this in above
we get
[tex]=x^{\frac{6}{3}\times\frac{1}{3}}[/tex]
Also by using the property
[tex](x^{a} )^{b} = x^{ab}[/tex]
We get[tex]=x^{\frac{6}{9}}[/tex]
Therefore expression becomes
[tex]= x^{\frac{2}{3}}[/tex]
Hence proved
Three less than two times a number equals four times the number plus eight. Create an equation based on this and solve.
2x-3=4x+8 Equation
-3=6x+8 Add 2x to opposite side
-11=6x Subtract 8.
x= -6/11 Answer